If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15y = 5(x + y) 10x + 15y = (x * 5 + y * 5) 10x + 15y = (5x + 5y) Solving 10x + 15y = 5x + 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10x + -5x + 15y = 5x + -5x + 5y Combine like terms: 10x + -5x = 5x 5x + 15y = 5x + -5x + 5y Combine like terms: 5x + -5x = 0 5x + 15y = 0 + 5y 5x + 15y = 5y Add '-15y' to each side of the equation. 5x + 15y + -15y = 5y + -15y Combine like terms: 15y + -15y = 0 5x + 0 = 5y + -15y 5x = 5y + -15y Combine like terms: 5y + -15y = -10y 5x = -10y Divide each side by '5'. x = -2y Simplifying x = -2y
| x^2-99x-2=0 | | e^7x+1=14 | | 8y^2-3y+5y^2-4y= | | (6-2)4+2(8-5)= | | 3p^2-5p-28=0 | | h^2=6h+16 | | 5x=3x-5 | | -3t^3=-11t^2-20t | | 20v^2=7v+3 | | T-21=14 | | (k+5)(k-1)=-8 | | 3p^3-75p=3p^2-75 | | 10x+5=23 | | 3z^4=3z^2 | | x^4+28=11x^2 | | 2b+3a= | | 9x+30=2x^2 | | 9c+6= | | 5x+5x=20 | | Log[5](6x+1)=2 | | 15-2=52x | | (7x^2-4x-5)+(6x^2-x+2)= | | 3(-1x-3)=0 | | 6(-7x+5)=30 | | x*2+4x-1=0 | | 4(10-5x)=0 | | 5(7+3x)=-100 | | -5(5x-10)=325 | | -2(2-4x)=52 | | 2(u-2)=9u+8-2(-4u-3) | | f(x)=1.2 | | -7+4x=-4x-95 |